2010
DOI: 10.1016/j.gca.2009.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Natural iodine in a clay formation: Implications for iodine fate in geological disposals

Abstract: Iodine is one of the most problematic radioisotopes in the context of nuclear waste geological disposal due to its high mobility. Considerable effort has been dedicated to the measurement of its potential retardation during diffusive transport leading to conflicting results, from no retardation to significant retardation, leading in turn to considerable debate. The present study aims at providing new insights into this aspect of the iodine problem by careful quantification of iodine reservoirs in the Callovian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 55 publications
0
36
0
Order By: Relevance
“…Hu et al (2005) suggested that some inorganic iodine (I À or IO 3 À ) could be present by sorption to the mineral phase, which possesses positively charged surfaces. While it is possible that iodine (likely as iodate) can be trapped in the mineral pool such as carbonate (Claret et al, 2010), this is not the case for the soils of this study, since barely any inorganic carbon was detected based on the difference between the total carbon and total organic carbon of the whole soils (Electronic Annex EA-1). Other minerals (quartz, kaolinite, goethite, etc.)…”
Section: Importance Of Soil Organic Matter As a Radioiodine Sinkmentioning
confidence: 92%
See 1 more Smart Citation
“…Hu et al (2005) suggested that some inorganic iodine (I À or IO 3 À ) could be present by sorption to the mineral phase, which possesses positively charged surfaces. While it is possible that iodine (likely as iodate) can be trapped in the mineral pool such as carbonate (Claret et al, 2010), this is not the case for the soils of this study, since barely any inorganic carbon was detected based on the difference between the total carbon and total organic carbon of the whole soils (Electronic Annex EA-1). Other minerals (quartz, kaolinite, goethite, etc.)…”
Section: Importance Of Soil Organic Matter As a Radioiodine Sinkmentioning
confidence: 92%
“…Recently, Yamaguchi et al (2010) using iodine K-edge X-ray absorption near-edge structure (XANES) reported soil organic matter (SOM) is capable of oxidizing I À or reducing IO 3 À and subsequently binding iodine to reactive carbon sites. Even though it was apparently observed that a main reservoir for iodine can be the carbonate fraction in a Callovian-Oxfordian (COx) clay rock, one needs to consider the fact that organic matter contents in these clay materials under investigation were mostly below 1% (Claret et al, 2010). Li et al (2011) provided indirect evidence that iodide was enzymatically transported into the soil bacterial cell and incorporated into cellular components via covalent binding.…”
Section: Introductionmentioning
confidence: 99%
“…The mass ratios of different phases were extracted from the BRGM mineralogical database [40] considering the C2b2 lithostratigraphic level (see Fig. 2 in [41]). Illite and illite/smectite (I/S) were identified as the main clay phases of the COx claystone.…”
Section: Callovian-oxfordian Claystone Modelmentioning
confidence: 99%
“…Prevailing fossils are bivalves from the upper part of the benthos, but pelagic bivalves (posidonomya), sponges, foraminifers, brachiopods, and echinoderms from the deep benthos are also present. Previous observations of carbonate bioclasts were performed in the framework of the study of iodine in carbonates (Claret et al, 2010;Lerouge et al, 2010b). The diagenetic carbonates are virtually all micritic calcite forming the cement of the rock but minor 10 lmsized euhedral calcite and dolomite grains are also dispersed in the sediment (Buschaert et al, 2004;Gaucher et al, 2004;Clauer et al, 2007).…”
Section: Petrography -Previous Workmentioning
confidence: 99%